2023
DOI: 10.3390/coatings13030618
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Fracture Characteristics of Asphalt Mixtures in High Altitude and Cold Regions with Large Temperature Differences

Abstract: Due to the harsh climatic conditions in high altitude and cold regions with large temperature differences, asphalt pavement is generally prone to cracking, and the cracks propagate rapidly, which reduces the service life and service level of the road. The factors influencing the fracture characteristics of asphalt mixtures were analyzed in this paper, and the mixtures with different aggregate gradations from various types of asphalt were prepared. The fracture characteristics were explored using the thermal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, as the temperature decreases, the asphalt binder gradually becomes harder, reducing its ability to relax thermal stress, which results in a gradual accumulation of thermal stress. Wang et al [ 10 ] indicated that when the temperature drops below −18.6 °C, the thermal stress increases linearly. This is consistent with the findings of this study, where at this point, the thermal stress cannot be relaxed at all, and it increases linearly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the temperature decreases, the asphalt binder gradually becomes harder, reducing its ability to relax thermal stress, which results in a gradual accumulation of thermal stress. Wang et al [ 10 ] indicated that when the temperature drops below −18.6 °C, the thermal stress increases linearly. This is consistent with the findings of this study, where at this point, the thermal stress cannot be relaxed at all, and it increases linearly.…”
Section: Resultsmentioning
confidence: 99%
“…Qin et al [44] pointed out that there was a quantitative relationship between road surface temperature and atmospheric temperature, as shown in Equation (10). This equation can be used to estimate the road surface temperature based on atmospheric temperature.…”
Section: Comparison Of Thermal Stress In Different Regionsmentioning
confidence: 99%
See 1 more Smart Citation